Synthesis, characterization, photophysical properties, and catalytic activity of an SCS bis(N-heterocyclic thione) (SCS-NHT) Pd pincer complex1. Issue 32 (28th August 2015) - Tyson, Ginger E.; Tokmic, Kenan; Oian, Casey S.; Rabinovich, Daniel; Valle, Henry U.; Hollis, T. Keith; Kelly, John T.; Cuellar, Kristina A.; McNamara, Louis E.; Hammer, Nathan I.; Webster, Charles Edwin; Oliver, Allen G.; et al.
<x xml:space="preserve">Abstract</x> The first SCS-NHT pincer ligand and its Pd complex.